ANALISIS PENGARUH HARGA DOMESTIK, JUMLAH PRODUKSI, HARGA EKSOR, PENJUALAN DOMESTIK, NILAI TUKAR RUPIAH TERHADAP JUMLAH EKSPOR GONDORUKEM DI KBM GT 1 PERUM PERHUTANI GTD&MKP JATENG (MRANGGEN) - Lestari, Dini Silcy; Barokah, Siti Nur; Nurkhayati, Isnaeni - (Politeknik Negeri Semarang, 2015)
During this several period, the production ofGum Rosin produced by Perum Perhutani asthe only producer has given goodcontribution for the export development ofGum Rosin, Indonesia. The domestic sales isinclined to down, it happens caused theexistence of the substitution products formanufacturing the raw material of soap andthe wane of industry’s buying power. Thisstudy is trying to examine the factors thataffect the number of Gum Rosin export. Tounderstand whether the factor of Gum Rosindomestic price affect the number of GumRosin export, to understand the number ofGum Rosin production factors affect thenumber of Gum Rosin export, to understandthe export price factor affect the number ofGum Rosin export, to understand the domesticsales factor affect the number of Gum Rosinexport, to understand the exchange rate valuefactor affect the number of Gum Rosin export.The result of this research shows that variableof Gum Rosin domestic price, the number ofGum Rosin production, the Gum Rosin exportprice, the Gum Rosin domestic price and theexchange rate of rupiah, significantly effectstoward the number of Gum Rosin export inPerum Perhutani. The result of the researchidentified the flow of Gum Rosin based on themarket share, for all this time, the majormarket share of Gum Rosin Perum Perhutaniis India, but still lost out to China.